SFPQ Promotes Lung Cancer Malignancy via Regulation of CD44 v6 Expression - Yang, Libang; Yang, Jianbo; Jacobson, Blake; Gilbertsen, Adam; Smith, Karen; Higgins, LeeAnn; Guerrero, Candace; Xia, Hong; Henke, Craig A.; Lin, Jizhen (Frontiers in Oncology, 2022)
Mesenchymal stem cells (MSCs) contribute to tumor pathogenesis and elicit antitumor immune responses in tumor microenvironments. Nuclear proteins might be the main players in these processes. In the current study, combining spatial proteomics with ingenuity pathway analysis (IPA) in lung non-small cell (NSC) cancer MSCs, we identify a key nuclear protein regulator, SFPQ (Splicing Factor Proline and Glutamine Rich), which is overexpressed in lung cancer MSCs and functions to promote MSCs proliferation, chemical resistance, and invasion. Mechanistically, the knockdown of SFPQ reduces CD44v6 expression to inhibit lung cancer MSCs stemness, proliferation in vitro, and metastasis in vivo. The data indicates that SFPQ may be a potential therapeutic target for limiting growth, chemotherapy resistance, and metastasis of lung cancer.